Novel gradient structure thermal barrier coating resistant to CMAS corrosion and preparation method of novel gradient structure thermal barrier coating

By combining atmospheric plasma spraying and laser glazing treatment technology, a gradient structure thermal barrier coating is formed, which solves the problems of corrosion resistance and thermal conductivity of existing thermal barrier coatings when facing molten CMAS corrosion, and achieves excellent resistance Corrosion performance and low thermal conductivity.

CN119433407APending Publication Date: 2025-02-14NANCHANG HANGKONG UNIVERSITY

Patent Information

Application Number
CN202411632306.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing thermal barrier coatings are difficult to maintain corrosion resistance when facing molten CMAS corrosion, and the improvement of thermal conductivity also affects its performance.

Method used

The combination of atmospheric plasma spraying and laser glazing treatment technology is used to form a gradient structure thermal barrier coating. The coating consists of a spray-coated NiCrAlY bonding layer, an 8YSZ ceramic layer, a LaYbZrCeO7 ceramic layer and a laser-glazed LaYbZrCeO7 ceramic layer. This structure achieves excellent CMAS corrosion resistance and low thermal conductivity.

Benefits of technology

The excellent corrosion resistance of thermal barrier coating to molten CMAS at high temperatures is achieved, while maintaining low thermal conductivity and extending the service life of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433407A_ABST
    Figure CN119433407A_ABST
Patent Text Reader

Abstract

The invention discloses a CMAS corrosion resistant novel gradient structure thermal barrier coating and a preparation method thereof, and belongs to the technical field of thermal barrier coatings. The novel gradient structure thermal barrier coating comprises a base body, a spraying state NiCrAlY bonding layer, a spraying state 8YSZ ceramic layer, a spraying state LaYbZrCeO7 ceramic layer and a laser glazing LaYbZrCeO7 ceramic layer from bottom to top, the base body is made of nickel base alloy, and 8YSZ is ZrO2 stabilized by Y2O3 with the mass fraction of 8%. The design thought that the laser glazing compact ceramic layer and the spraying state porous ceramic layer are introduced into the thermal barrier coating structure is adopted, the excellent molten CMAS corrosion resistance can be achieved, meanwhile, the low thermal conductivity is achieved, and wide application prospects are achieved in the field of thermal barrier coating materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermal barrier coatings, and in particular to a CMAS corrosion-resistant gradient structure thermal barrier coating and a preparation method thereof. Background Art

[0002] Thermal barrier coating is a kind of thermal insulation and protective ceramic material, which can effectively improve the operating temperature and service life of aircraft engines, and has important economic value and strategic position in this field. LaYbZrCeO7 (25% LaO1.5-25% YbO1.5-25% ZrO2-25% CeO2, mol%) has excellent thermophysical properties such as low thermal conductivity and high thermal expansion coefficient, making it a ceramic material with great potential for thermal barrier coating. Traditional thermal barrier coating preparation technologies, such as atmospheric plasma spraying and physical vapor deposition, still cannot solve the problem of easy corrosion of thermal barrier coating by molten CMAS (CaO-MgO-Al2O3-SiO2). Experts and scholars have been exploring new preparation technologies for thermal barrier coatings in order to improve the corrosion resistance of the coating to molten CMAS. Laser glazing is a surface modification technology, which pre-coats a layer of ceramic or metal material on the surface of the substrate, and uses a high-intensity laser beam to complete the melting and re-solidification process of the coating material, so that it adheres to the surface of the substrate. This technology treats the surface of the thermal barrier coating, which can close some microcracks and pores in the coating, improve its density, and achieve the purpose of improving its resistance to molten CMAS corrosion. However, the reduction in the porosity of the thermal barrier coating will inevitably lead to an increase in the thermal conductivity of the coating. Therefore, the atmospheric plasma spraying and laser glazing treatment technology are combined and introduced into the preparation process of the thermal barrier coating to form a gradient structure thermal barrier coating, that is, the upper layer is a dense laser glazed ceramic layer, and the lower layer is a loose, porous sprayed ceramic layer. It is of great significance to develop a new type of gradient structure thermal barrier coating that has excellent resistance to molten CMAS corrosion and low thermal conductivity.

[0003] After searching, Chinese patent document CN111850454A discloses a thermal barrier coating resistant to CMAS erosion, which is composed of a bonding layer, a ceramic layer and an apatite phase barrier layer from bottom to top. The bonding layer is CoCrAlYTaSi material; the ceramic layer is a rare earth zirconate material, and its chemical formula is RE2Zr2O7, RE is any 1-2 different elements among Yb, La, Ce, Gd, and the molar ratio of RE element to the total elements is less than 20%; the thickness of the bonding layer is 50-150μm, the thickness of the ceramic layer is 100-300μm, and the thickness of the apatite phase barrier layer is 5-10μm. The invention mainly forms a dense apatite phase barrier layer on the surface. This layer has the characteristics of high melting point, high density, good phase stability, and strong bonding force. It can not only fill the inevitable holes and cracks on the surface of the ceramic layer during the spraying process, but also block the CMAS diffusion channel inside the ceramic layer, effectively improving the thermal barrier coating's ability to resist CMAS erosion.

[0004] Chinese patent document CN109706418A discloses a dual-ceramic layer structure 8YSZ thermal barrier coating and a preparation method thereof, wherein the thermal barrier coating comprises a bonding layer, an 8YSZ transition layer and an 8YSZ top layer from bottom to top, wherein the bonding layer thickness is 50-150 μm, the transition layer thickness is 20-60 μm, and the top layer thickness is 200-400 μm. The bonding layer is an MCrAl Y metal bonding layer, wherein the bonding layer surface roughness Ra is 4-6 μm, Rz is 25-45 μm, RSm is 140-180 μm, and Rsk is 0.05-0.25. The invention mainly prepares a nano dual-ceramic layer structure thermal barrier coating of a plasma spray of a nanostructure transition layer + a nanostructure top layer, and a plasma sprayed dual-ceramic layer structure thermal barrier coating of a layered structure transition layer + a nanostructure top layer. Compared with a single ceramic layer structure thermal barrier coating, the bonding strength, thermal shock resistance and thermal cycle life of the thermal barrier coating are improved.

[0005] Chinese patent document CN117488230A discloses a high-temperature gradient structure thermal barrier coating and its preparation method. The high-temperature gradient structure thermal barrier coating of the invention has a structure from bottom to top of substrate, bonding layer, 8YSZ layer, and rare earth zirconate layer. The bonding layer is NiCrAlY alloy; the 8YSZ layer is ZrO2 stabilized with Y2O3 containing 8% by mass; the chemical composition of the rare earth zirconate layer is LaYbZrCeO7. The invention introduces rare earth doping and double-layer structure design ideas into the thermal barrier coating structure, which can obtain low thermal conductivity, high thermal expansion coefficient and excellent thermal cycle life, and has broad application prospects in the field of thermal barrier coating materials.

[0006] After searching, it was found that no prior art had been developed that combined atmospheric plasma spraying and laser glazing treatment technology and introduced into the preparation process of thermal barrier coating to form a gradient structure thermal barrier coating, so that it has excellent resistance to molten CMAS corrosion and low thermal conductivity, thus the present invention was created. Summary of the invention

[0007] In view of this, in order to solve the above technical problems, the purpose of the present invention is to provide a new gradient structure thermal barrier coating and a preparation method thereof, wherein the new gradient structure thermal barrier coating has excellent resistance to molten CMAS corrosion.

[0008] The technical solutions adopted are:

[0009] The invention discloses a novel gradient structure thermal barrier coating resistant to CMAS corrosion, which comprises, from bottom to top, a substrate, a sprayed NiCrAlY bonding layer, a sprayed 8YSZ ceramic layer, a sprayed LaYbZrCeO7 ceramic layer and a laser glazed LaYbZrCeO7 ceramic layer, wherein the substrate is a nickel-based alloy, and 8YSZ is ZrO2 stabilized with Y2O3 containing 8% by mass.

[0010] Furthermore, the mass percentage ratio of the sprayed NiCrAlY bonding layer is: Ni 69%, Cr 24.90%, Al 5.5%, Y 0.60%.

[0011] Furthermore, the sprayed NiCrAlY bonding layer, the sprayed 8YSZ ceramic layer, and the sprayed LaYbZrCeO7 ceramic layer are all layered structures; and / or the laser glazed LaYbZrCeO7 ceramic layer is a dense layer.

[0012] Furthermore, both the sprayed LaYbZrCeO7 and laser glazed LaYbZrCeO7 ceramic layers have defective fluorite phase structures.

[0013] Further, the thickness of the laser glazed LaYbZrCeO7 ceramic layer is 64-68 μm, the thickness of the sprayed LaYbZrCeO7 ceramic layer is 30-33 μm, the thickness of the sprayed 8YSZ layer is 163-167 μm, and the thickness of the sprayed NiCrAlY bonding layer is 32-36 μm. For example, the thickness of the laser glazed LaYbZrCeO7 ceramic layer is 66 μm, the thickness of the sprayed LaYbZrCeO7 ceramic layer is 32 μm, the thickness of the sprayed 8YSZ layer is 165 μm, and the thickness of the sprayed NiCrAlY bonding layer is 34 μm.

[0014] A method for preparing a novel gradient structure thermal barrier coating resistant to CMAS corrosion according to any of the above schemes of the present invention comprises the following steps:

[0015] S1. Atomized particles: NiCrAlY, 8YSZ, LaYbZrCeO7 atomized particles are placed in a drying oven and dried for later use;

[0016] S2. Surface treatment of nickel-based alloy substrate: The nickel-based alloy substrate is degreased, cleaned, and sandblasted in sequence;

[0017] S3. Thermal spraying NiCrAlY bonding layer: using atmospheric plasma spraying technology to prepare NiCrAlY bonding layer on nickel-based alloy substrate;

[0018] S4. Thermal spraying 8YSZ ceramic layer: 8YSZ ceramic layer was prepared on the NiCrAlY bonding layer using atmospheric plasma spraying technology;

[0019] S5. Thermal spraying of LaYbZrCeO7 ceramic layer: LaYbZrCeO7 ceramic layer was prepared on 8YSZ ceramic layer by atmospheric plasma spraying technology;

[0020] S6. Laser glazing treatment: laser glazing the surface of the LaYbZrCeO7 ceramic layer to prepare a laser glazed LaYbZrCeO7 ceramic layer.

[0021] Furthermore, in S1, the atomized particle size of Ni CrAl Y is 32-52 μm, the atomized particle size of 8YSZ is 45-70 μm, and the atomized particle size of LaYbZrCeO7 is 30-52 μm.

[0022] Further, in S3, the atmospheric plasma spraying conditions of the NiCrAlY bonding layer include: arc current of 600A, arc voltage of 70V, argon flow rate of 40L / min, hydrogen flow rate of 10L / min, spraying distance of 110mm, powder feeding rate of 50g / min, and spray gun moving rate of 500mm / min;

[0023] And / or, in S4, the atmospheric plasma spraying conditions of the 8YSZ ceramic layer include: arc current of 630A, arc voltage of 70V, argon flow rate of 40L / min, hydrogen flow rate of 12L / min, spraying distance of 100mm, powder feeding rate of 45g / min, and spray gun moving rate of 500mm / min.

[0024] Furthermore, in S5, the atmospheric plasma spraying conditions of the LaYbZrCeO7 ceramic layer include: arc current of 650A, arc voltage of 72V, argon flow rate of 40L / min, hydrogen flow rate of 12L / min, spraying distance of 100mm, powder feeding rate of 42g / min, and spray gun moving rate of 500mm / min.

[0025] Furthermore, in S6, the laser glazing treatment conditions include: laser power of 300 W, scanning speed of 360 mm / min, spot diameter of 3 mm, argon gas flow rate of 20 L / min, and spot overlap of 0.8 mm.

[0026] The beneficial effects of the present invention are:

[0027] The novel gradient structure thermal barrier coating of the present invention has a three-layer ceramic layer structure, which is a top laser glazed LaYbZrCeO7 ceramic layer, an intermediate sprayed LaYbZrCeO7 ceramic layer and a bottom sprayed 8YSZ ceramic layer, and has excellent resistance to molten CMAS corrosion and low thermal conductivity, and is expected to be applied in the field of thermal barrier coatings. At the same time, the method of the present invention also has the advantages of simple preparation process, high efficiency, low cost, strong controllability, and easy scale realization. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 XRD patterns of sprayed LaYbZrCeO7 coating before and after laser glazing treatment.

[0029] Figure 2 Cross-sectional morphology of sprayed LaYbZrCeO7 / 8YSZ and laser glazed LaYbZrCeO7 / 8YSZ thermal barrier coatings.

[0030] Figure 3 Cross-sectional morphology of sprayed LaYbZrCeO7 / 8YSZ and laser glazed LaYbZrCeO7 / 8YSZ thermal barrier coatings after CMAS corrosion at 1300℃ for 10 min.

[0031] Figure 4 Cross-sectional morphology of sprayed LaYbZrCeO7 / 8YSZ and laser glazed LaYbZrCeO7 / 8YSZ thermal barrier coatings after CMAS corrosion at 1300℃ for 30min. DETAILED DESCRIPTION

[0032] The present invention is described in detail below through specific examples, but the use and purpose of these exemplary implementation modes are only used to illustrate the present invention, and do not constitute any form of limitation on the actual protection scope of the present invention, nor limit the protection scope of the present invention to them.

[0033] Example 1

[0034] A method for preparing a novel gradient structure thermal barrier coating in this embodiment includes the following steps:

[0035] S1. Ni CrAlY, 8YSZ, LaYbZrCeO7 atomized particles are placed in a drying oven to dry and set aside.

[0036] S2. The surface of the nickel-based alloy (GH4169) substrate is degreased, cleaned, and sandblasted in sequence;

[0037] S3. Thermal spraying NiCrAlY bonding layer: A NiCrAlY bonding layer was prepared on a nickel-based alloy substrate by atmospheric plasma spraying technology, and the mass percentage of its components was Ni 69%, Cr24.90%, Al 5.50%, and Y 0.60%; the spraying conditions of the NiCrAlY bonding layer included: arc current of 600A, arc voltage of 70V, argon flow rate of 40L / min, hydrogen flow rate of 10L / min, spraying distance of 110mm, powder feeding rate of 50g / min, spray gun moving rate of 500mm / min, and its thickness was 34μm.

[0038] S4. Thermal spraying of 8YSZ ceramic layer: The 8YSZ ceramic layer was prepared on the NiCrAlY bonding layer using atmospheric plasma spraying technology. The spraying conditions included: arc current of 630A, arc voltage of 70V, argon flow rate of 40L / min, hydrogen flow rate of 12L / min, spraying distance of 100mm, powder feeding rate of 45g / min, spray gun moving rate of 500mm / min, and thickness of 165μm.

[0039] S5. Thermal spraying of LaYbZrCeO7 ceramic layer: LaYbZrCeO7 ceramic layer was prepared on 8YSZ ceramic layer by atmospheric plasma spraying technology. The spraying conditions included arc current of 650A, arc voltage of 72V, argon flow rate of 40L / min, hydrogen flow rate of 12L / min, spraying distance of 100mm, powder feeding rate of 42g / min, spray gun moving rate of 500mm / min, and thickness of 98μm.

[0040] S6. Laser glazing treatment: The surface of the LaYbZrCeO7 ceramic layer is treated with laser glazing to prepare a layer of laser glazed LaYbZrCeO7 ceramic layer. The laser glazing treatment conditions include: laser power of 300W, scanning speed of 360mm / min, spot diameter of 3mm, argon flow rate of 20L / min, spot overlap of 0.8mm, and thickness of 66μm.

[0041] The obtained thermal barrier coating is recorded as laser glazed LaYbZrCeO7 / 8YSZ.

[0042] Comparative Example 1

[0043] Referring to Example 1, this comparative example only repeats steps S1-S5 in Example 1.

[0044] The obtained thermal barrier coating is recorded as sprayed LaYbZrCeO7 / 8YSZ.

[0045] CMAS (33CaO-9MgO-13AlO1.5-45SiO2, mol%) powder was heated at 30 mg / cm 2 The deposition amount was evenly coated on the surface of the prepared laser glazed LaYbZrCeO7 / 8YSZ and sprayed LaYbZrCeO7 / 8YSZ thermal barrier coating samples to carry out CMAS corrosion experiments, in order to better show the CMAS corrosion resistance of laser glazed LaYbZrCeO7 / 8YSZ.

[0046] Figure 1 This is the XRD pattern of the sprayed LaYbZrCeO7 coating before and after laser glazing treatment.

[0047] like Figure 1 As shown, the sprayed LaYbZrCeO7 coating always has a defective fluorite (Fm-3m) phase structure before and after laser glazing treatment.

[0048] Figure 2 The cross-sectional morphology of sprayed LaYbZrCeO7 / 8YSZ and laser glazed LaYbZrCeO7 / 8YSZ thermal barrier coatings.

[0049] like Figure 2 As shown, the thicknesses of the sprayed LaYbZrCeO7 ceramic layer, the sprayed 8YSZ ceramic layer and the sprayed NiCrAlY bonding layer in the sprayed LaYbZrCeO7 / 8YSZ thermal barrier coating are approximately 98, 165 and 34 μm, respectively; the thicknesses of the laser glazed LaYbZrCeO7 ceramic layer, the sprayed LaYbZrCeO7 ceramic layer, the sprayed 8YSZ ceramic layer and the sprayed NiCrAlY bonding layer in the laser glazed LaYbZrCeO7 / 8YSZ thermal barrier coating are approximately 66, 32, 165 and 34 μm, respectively.

[0050] CMAS corrosion resistance test 1:

[0051] Based on Example 1, Figure 3 The cross-sectional morphology of the sprayed LaYbZrCeO7 / 8YSZ and laser glazed LaYbZrCeO7 / 8YSZ thermal barrier coatings after CMAS corrosion at 1300℃ for 10 min.

[0052] Depend on Figure 3It can be seen that after 10 minutes of molten CMAS corrosion at 1300°C, the CMAS corrosion depth of the laser-glazed LaYbZrCeO7 / 8YSZ thermal barrier coating is only about 4.5um, which is much smaller than the sprayed LaYbZrCeO7 / 8YSZ thermal barrier coating (about 7.0um), indicating that the laser-glazed LaYbZrCeO7 / 8YSZ thermal barrier coating has excellent anti-CMAS corrosion performance. Figure 3 It can also be seen that points 1 and 3 in the reaction layer contain all the elements of CMAS and RE-ZrO2, which are RE'-ZrO2 ceramic particles formed in the "dissolution-reprecipitation" process. Points 2 and 4 only contain Ca, Si, RE and Zr, without Ma and AI elements, and are highly dense and high melting point corrosion products, rare earth apatite phase. Therefore, the reaction layer is composed of RE'-ZrO2 ceramic and rare earth apatite phase.

[0053] CMAS corrosion resistance test 2:

[0054] Based on Example 1, Figure 4 The cross-sectional morphology of the sprayed LaYbZrCeO7 / 8YSZ and laser glazed LaYbZrCeO7 / 8YSZ thermal barrier coatings after CMAS corrosion at 1300℃ for 30 minutes.

[0055] like Figure 4 As shown in the figure, after 30 minutes of molten CMAS corrosion at 1300°C, the CMAS corrosion depth of the laser-glazed LaYbZrCeO7 / 8YSZ thermal barrier coating is only about 6.4um, which is much smaller than the sprayed LaYbZrCeO7 / 8YSZ thermal barrier coating (about 13.1um), which once again shows that the laser-glazed LaYbZrCeO7 / 8YSZ thermal barrier coating exhibits excellent resistance to CMAS corrosion.

[0056] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention. They are not intended to limit the scope of protection of the present invention. All equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.

Claims

1. A new type of gradient structure thermal barrier coating resistant to CMAS corrosion, characterized in that: It includes a substrate, a sprayed NiCrAlY bonding layer, a sprayed 8YSZ ceramic layer, a sprayed LaYbZrCeO7 ceramic layer and a laser glazed LaYbZrCeO7 ceramic layer from bottom to top, wherein the substrate is a nickel-based alloy, and 8YSZ is ZrO2 stabilized with 8% by mass of Y2O3.

2. The novel gradient structure thermal barrier coating resistant to CMAS corrosion according to claim 1, characterized in that: The mass percentage ratio of the sprayed NiCrAlY bonding layer is: Ni 69%, Cr 24.90%, Al 5.5%, and Y 0.60%.

3. The novel gradient structure thermal barrier coating resistant to CMAS corrosion according to claim 1, characterized in that: The sprayed NiCrAlY bonding layer, the sprayed 8YSZ ceramic layer, and the sprayed LaYbZrCeO7 ceramic layer are all layered structures; and / or the laser glazed LaYbZrCeO7 ceramic layer is a dense layer.

4. The novel gradient structure thermal barrier coating resistant to CMAS corrosion according to claim 1, characterized in that: Both the sprayed LaYbZrCeO7 and laser glazed LaYbZrCeO7 ceramic layers have defective fluorite phase structures.

5. The novel gradient structure thermal barrier coating resistant to CMAS corrosion according to claim 1, characterized in that: The thickness of the laser glazed LaYbZrCeO7 ceramic layer is 64-68 μm, the thickness of the sprayed LaYbZrCeO7 ceramic layer is 30-33 μm, the thickness of the sprayed 8YSZ layer is 163-167 μm, and the thickness of the sprayed NiCrAlY bonding layer is 32-36 μm.

6. A method for preparing a novel gradient structure thermal barrier coating resistant to CMAS corrosion according to any one of claims 1 to 5, characterized in that: The steps include: S1. Atomized particles: NiCrAlY, 8YSZ, LaYbZrCeO7 atomized particles are placed in a drying oven and dried for later use; S2. Surface treatment of nickel-based alloy substrate: The nickel-based alloy substrate is degreased, cleaned, and sandblasted in sequence; S3. Thermal spraying NiCrAlY bonding layer: using atmospheric plasma spraying technology to prepare NiCrAlY bonding layer on nickel-based alloy substrate; S4. Thermal spraying of 8YSZ ceramic layer: using atmospheric plasma spraying technology to prepare 8YSZ ceramic layer on NiCrAlY bonding layer; S5. Thermal spraying of LaYbZrCeO7 ceramic layer: LaYbZrCeO7 ceramic layer was prepared on 8YSZ ceramic layer by atmospheric plasma spraying technology; S6. Laser glazing treatment: laser glazing the surface of the LaYbZrCeO7 ceramic layer to prepare a laser glazed LaYbZrCeO7 ceramic layer.

7. The method for preparing the novel gradient structure thermal barrier coating resistant to CMAS corrosion according to claim 6, characterized in that: In S1, the atomized particle size of NiCrAlY is 32-52 μm, the atomized particle size of 8YSZ is 45-70 μm, and the atomized particle size of LaYbZrCeO7 is 30-52 μm.

8. The method for preparing the novel gradient structure thermal barrier coating resistant to CMAS corrosion according to claim 6, characterized in that: In S3, the atmospheric plasma spraying conditions of the NiCrAlY bonding layer included: arc current of 600 A, arc voltage of 70 V, argon flow rate of 40 L / min, hydrogen flow rate of 10 L / min, spraying distance of 110 mm, powder feeding rate of 50 g / min, and spray gun moving rate of 500 mm / min; And / or, in S4, the atmospheric plasma spraying conditions of the 8YSZ ceramic layer include: arc current of 630A, arc voltage of 70V, argon flow rate of 40L / min, hydrogen flow rate of 12L / min, spraying distance of 100mm, powder feeding rate of 45g / min, and spray gun moving rate of 500mm / min.

9. The method for preparing the novel gradient structure thermal barrier coating resistant to CMAS corrosion according to claim 6, characterized in that: In S5, the atmospheric plasma spraying conditions of the LaYbZrCeO7 ceramic layer include: arc current of 650A, arc voltage of 72V, argon flow rate of 40L / min, hydrogen flow rate of 12L / min, spraying distance of 100mm, powder feeding rate of 42g / min, and spray gun moving rate of 500mm / min.

10. The method for preparing the novel gradient structure thermal barrier coating resistant to CMAS corrosion according to claim 6, characterized in that: In S6, the laser glazing treatment conditions include: laser power of 300 W, scanning speed of 360 mm / min, spot diameter of 3 mm, argon gas flow rate of 20 L / min, and spot overlap of 0.8 mm.

Citation Information

Patent Citations

  • Double-ceramic-layer structure 8YSZ thermal barrier coating and preparation method

    CN109706418A

  • Thermal barrier coating layer resisting CMAS erosion and preparation method

    CN111850454A

  • Thermal barrier coating with high-temperature gradient structure and preparation method of thermal barrier coating

    CN117488230A

Cited By

  • Multi-element rare earth modified zirconium oxide double-layer thermal barrier coating and preparation method thereof

    CN122484686A